Me he tāheke te wai i aku kamo = Waterfalls of tears : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters in Māori Visual Arts, Massey University, Palmerston North, New Zealand - Waitai, Raukurawaihoea Naani Jane Whakaipo (Massey University, 2022)
This report provides context to the conceptual development of 'Me he tāheke te wai i aku kamo - Waterfalls of Tears'. It has as its fundamental presumption that we are wai and we belong to wai. The work is the subjective response of an uri of Whanganui iwi to the diversion of sacred headwaters to create hydro-electricity for the nation. The accounts given by iwi elders during an extensive period of litigation activated the mouri from which the work was conceived and realised. Consequently this report documents a navigation through the intangible field of emotion, wairuatanga and the metaphysical. Post-contact visual representation of Whanganui iwi, wai and whenua highlights the focus of the colonial lens to be commercially motivated whereas that of the indigenous lens to be grounded in kaupapa. The works of a range of contemporary artists who portray dimensions of wairuatanga and emotion are explored. A consideration of conceptual forms including puna mahara conclude that form is conceived by the conceiver and that form carries cultural connotations open to interpretation depending on the worldview of the participants. The work is non-customary, non-explicit and largely non-implicit. It lacks both visual correspondence and empathy to customary models. Paradoxically its conception remains firmly anchored within the tikanga and mātauranga of an iwi who see themselves as a direct reflection of their ancestral waters.
Copyright holders of possibly copyrighted images may request removal using the "Copyright Take Down Request" link below.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)